Association Between Socioeconomic Status, Food Security, and Dietary Diversity Among Sociology Students at the Central University of Venezuela - Hernández, Pablo; Camardiel, Alberto (Frontiers in Sustainable Food Systems, 2021)
Venezuela is currently in a difficult social, political, and economic situation that has exposed people to many factors, including socioeconomic disadvantages, food insecurity, and lack of access to healthy and nutritious foods. These factors are associated with low dietary diversity, especially for economically dependent university students. In this study, we aimed to identify the associations between socioeconomic status, food security, and dietary diversity among sociology students at the Central University of Venezuela (UCV). This cross-sectional study was conducted between June and November 2016 on a simple random sample of 270 students. Indicators were calculated using data collected by the Mendez-Castellano socioeconomic questionnaire, the Community Childhood Hunger Identification Projects Scale of Food Security adapted and validated for Venezuelans (Cronbach's alpha = 0.898), and the validated dietary diversity scale for individuals. The rate response was 100%. It was observed that most of the sample is located between the socioeconomic status of the rich and middle class (82.6%), presents some degree of food insecurity (85.9%), and maintains a diet with low dietary diversity (54.8%). Our main finding is that the socioeconomic status in the households of those students is not associated with either their food security level or their dietary diversity, but these constructs are related in a significant statistical way. In particular, the odds of a student household having a diverse diet instead of a monotonous diet are 3.92 (95% CI: 2.91; 4.93) times greater for those in food security instead of moderate/severe food insecurity. It is concluded that these students have a multifactorial critical food situation, in which the food right is violated, which could affect their permanence and academic performance.